Chemical Vapor Deposition for the Fabrication of WTe2/h‐BN Heterostructures - Andrejs Terehovs; Aris Jansons; Darja Dolbe; Jānis Švirksts; Jevgenijs Gabrusenoks; Anatolijs Sarakovskis; Gunta Kunakova (Advanced Materials Interfaces, 2025)
Abstract Tungsten ditelluride (WTe2) is a transition metal dichalcogenide with exotic properties, such as the quantum spin Hall effect, which has been demonstrated in monolayer WTe2 heterostructures with h‐BN. So far, these studies have relied on heterostructure fabrication via exfoliation, while direct growth methods to produce high‐quality 2D WTe2 on hexagonal boron nitride remain a challenge. Systematic studies of chemical vapor deposition (CVD) using NaCl as a seeding promoter are reported to produce WTe2 crystals with different morphologies on Si/SiO2 and Si/SiO2/h‐BN (exfoliated flakes or CVD monolayer) substrates. The formation of vertical WTe2/h‐BN heterostructures can be achieved by using a slightly increased growth temperature as compared to SiO2 substrates, and characterization, including Raman and XPS studies, confirms the successful growth of high‐quality WTe2 on h‐BN. This is further verified by magnetotransport measurements at low temperatures.